1989
DOI: 10.1128/mcb.9.3.1342
|View full text |Cite
|
Sign up to set email alerts
|

Cell-specific activity of the modulator region in the human cytomegalovirus major immediate-early gene.

Abstract: In this paper we demonstrate that modulator sequences upstream of the enhancer of the major immediateearly promoter of human cytomegalovirus exert a differential effect on the level of transcription in a variety of cells and that this region has the capacity to interact with specific nuclear protein. Depending on the cell type, these modulator sequences increased or decreased transcriptional activation from the IEl gene promoterenhancer. The cell lines identified in this report should be useful to study the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 21 publications
(23 reference statements)
1
42
0
Order By: Relevance
“…In transient expression assays this element was able to modulate gene expression in non-permissive cells in a negative manner, whereas it positively influences expression in permissive cells (Nelson et al, 1987). This was confirmed by in vitro transcription studies in which nuclear extracts of various cell lines were tested for their ability to mediate transcription in the presence or absence of the IE1 upstream region between positions -1145 and -524 (Lubon et al, 1989). This region, also referred to as the modulator region, participates in certain cell lines in transcriptional repression, whereas it augments transcription in other cells.…”
Section: Regulatory Elements In the Ie1 Upstream Regionmentioning
confidence: 62%
See 1 more Smart Citation
“…In transient expression assays this element was able to modulate gene expression in non-permissive cells in a negative manner, whereas it positively influences expression in permissive cells (Nelson et al, 1987). This was confirmed by in vitro transcription studies in which nuclear extracts of various cell lines were tested for their ability to mediate transcription in the presence or absence of the IE1 upstream region between positions -1145 and -524 (Lubon et al, 1989). This region, also referred to as the modulator region, participates in certain cell lines in transcriptional repression, whereas it augments transcription in other cells.…”
Section: Regulatory Elements In the Ie1 Upstream Regionmentioning
confidence: 62%
“…This region, also referred to as the modulator region, participates in certain cell lines in transcriptional repression, whereas it augments transcription in other cells. This suggests a cell-type specific regulatory mechanism of IE1 gene expression (Lubon et al, 1989).…”
Section: Regulatory Elements In the Ie1 Upstream Regionmentioning
confidence: 99%
“…For example, there are numerous nuclear factor-1 (NF-1) sites within the MIEP and the 18 and 19 bp repeat sequences contain NF-kB and cyclic AMPresponsive element binding protein (CREB) binding sites respectively (Meier & Stinski, 1996). Conversely, several studies using non-permissive cells have shown that the modulator and the 21 bp repeats are responsible for the inhibition of MIEP activity in such cells (Nelson et al, 1987;Lubon et al, 1989;Kothari et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…For example, there are numerous nuclear factor-1 (NF-1) sites within the MIEP and the 18 and 19 bp repeat sequences contain NF-kB and cyclic AMPresponsive element binding protein (CREB) binding sites respectively (Meier & Stinski, 1996). Conversely, several studies using non-permissive cells have shown that the modulator and the 21 bp repeats are responsible for the inhibition of MIEP activity in such cells (Nelson et al, 1987;Lubon et al, 1989;Kothari et al, 1991).In vivo, monocytes have been identified as an important site of HCMV latency (Taylor-Wiedeman et al, 1991); these cells carry the viral genome in the absence of lytic (productive) gene expression. Experiments in our laboratory and those of others have shown that the differentiation of peripheral blood monocytes to macrophages (monocytederived macrophages; MDMs) results in the induction of endogenous HCMV IE gene expression and reactivation of virus (Taylor-Wiedeman et al, 1994;Soderberg-Naucler et al, 1997).…”
mentioning
confidence: 99%
“…The HCMV promoter is strongly influenced by an upstream enhancer region with binding sites for various cellular transcription factors (Boshart et al, 1985;Niller & Henninghausen, 1991;Stinski & Roehr, 1985;Thomsen et al, 1984). Upstream of the enhancer region there is a modulator region which regulates the cell-type-specific expression of HCMV by binding further cell-specific transcription factors (Lubon et al, 1989).…”
mentioning
confidence: 99%